Well-being and tourism: A systematic literature review - Chryssoula Konstantopoulou; Sotirios Varelas; Panagiōtēs Liarnkobas (Economies, 2024)
In recent decades, the concept of well-being has often been the subject of psychological studies. The current study examines how tourism relates to well-being from the perspective of tourists/visitors, through the study of the older and more recent literature. Especially when it comes to the complex and multifaceted issue of well-being, in relation to the also complex and sensitive sectors of tourism, the specificity of this relationship is reflected in the evidence and the growing number of articles published in mainstream and reliable journals. By using the PRISMA framework, this article compares and evaluates published papers on the study of well-being and tourist behavior to guide and direct future research. It has been found that the relationship between well-being and tourism, especially after the emergence of the COVID-19 pandemic, has been significantly strengthened. This study highlights the need to adopt a holistic approach that considers all the connections between well-being and tourism.
Keywords: 330; well-being; tourism; risk perception; pandemic COVID-19